Constraints on Io's interior from auroral spot oscillations. Issue 2 (20th February 2017) - Roth, Lorenz; Saur, Joachim; Retherford, Kurt D.; Blöcker, Aljona; Strobel, Darrell F.; Feldman, Paul D.
Abstract: The morphology of Io's aurora is dominated by bright spots near the equator that oscillate up and down in approximate correlation with the oscillating orientation of the Jovian magnetospheric field. Analyzing Hubble Space Telescope images, we find that the auroral spots oscillate in phase with the time‐variable Jovian magnetic field at Io and that the amplitude of the spot oscillations is reduced by 15% (±5%) with respect to the amplitude of the magnetic field oscillation. We investigate the effects of Io's plasma interaction and magnetic induction in the moon's interior on the magnetic field topology and the aurora oscillations using a magnetohydrodynamic (MHD) simulation and an analytical induction model. The results from the MHD simulation suggest that the plasma interaction has minor effects on the oscillations, while the magnetic induction generally reduces magnetic field oscillations near the surface. However, the analytical model shows that induction in any near‐surface layer for which the skin depth is larger than the thickness—like a conductive magma ocean—would induce a phase shift, in conflict with the observations. Under the assumption that the spot oscillations represent the magnetic field oscillation, we constrain the conductance of a near‐surface layer to 1 × 10 3 S or lower. A magma ocean with conductances of 10 4 S or higher as derived from Galileo magnetometer measurements would cause overly strong attenuation of the amplitude in addition to the irreconcilable phase shift. The observed weakly attenuated, in‐phase spot oscillation is consistent with induction in a deep, highly conductive layer like Io's metallic core. Key Points: The amplitude of Io's auroral spot oscillations is reduced by 15% with respect to the amplitude of the Jovian magnetic field oscillation A conductive magma ocean should induce strong attenuation and a phase shift in the spot oscillations and appears inconsistent with the data The reduction of the spot oscillations is consistent with magnetic induction from a deep, highly conductive layer like Io's metallic core